Tillering Dynamics in Aromatic Rice Genotypes - Shahidullah, S. M.; Musa, Mohamed Hanafi; Md Ashrafuzzaman; Ismail, Mohd Razi; Salam, M. Abdus (2009)
An experiment was conducted with thirty aromatic rice genotypes to evaluate the tillering patterns and to explore its relationship with grain yield. Much variation was observed in tillering dynamics among the genotypes. Nineteen genotypes reached to peak population around 40 days after transplantation (DAT), when after tiller numbers started to reduce; 10 of them showed tillering climax at 50 DAT and only Kalijira Tapl-73 at 60 DAT. Maximum number of tillers varied from 136(Khazar) to 455/m2 (Chinigura). The highest rate of tiller mortality was found 49.29% in Chinigura and lowest in Jesso balam(10.10%). Sakkor khora produced highest number of panicles (277), whereas Khazar proved its worst performance with 90 panilces/m2. Among the aromatic rice genotypes in the current study, Elai produced higest grain yield (3.35 t/ha). The lowest yield was harvested 1.42 t/ha from Khazar. The number of panicles was positively correlated with maximum number of tillers(r = 0.76) and grain yield (r = 0.62). Total number of tillers at harvest had the biggest direct effect on grain yield. Number of panicles had insignificant direct effect on yield; however it created a large indirect effect through the total number of tillers. Number of tillers at all stages imposed considerable indirect effects through number of panicles.